Comparative study of vitamin B12 and holotranscobalamin or active B12 as a marker for vitamin B12 deficiency at Dr George Mukhari Hospital - Murray, Louise M. (University of Limpopo (Medunsa Campus), 2012)
Abstract Aim: This study was undertaken to compare the diagnostic sensitivity and specificity of total vitamin B 12 analyses to active B 12 (holoTC) analyses in a population of patients attending the Dr George Mukhari Hospital in Pretoria. Methods: Routine serum folate, full blood count (FBC), thyroid function test, homocysteine, serum total vitamin B 12 and active B 12 analyses were performed on 30 samples. Results: Serum folate was determined in all patients and 96% of the patients had a normal folate value. When looking at the FBC results it is important to note that three times as many males as females presented with anemia (36% versus 16%). Thyroid function tests were normal in 90% of patients. When the total vitamin B 12 test was preformed only 10% of patients tested positive for vitamin B 12 deficiency, in contrast to the active B12 analyses where 16% of patients tested positive for vitamin B12 deficiency. Both tests had a diagnostic sensitivity of 50%. The diagnostic specificity for total vitamin B12 was 93% in comparison with the 86% obtained by the active B12 analyses; when homocysteine was used as the true marker for vitamin B12 deficiency. Conclusion: Diagnostic sensitivity was the same and the total vitamin B12 test's specificity was better in comparison to the active B 12 analyses. Thus the active B 12 assay cannot be recommended for routine use, since it has no benefit.
Thesis (M Med (Chemical Pathology)) -- University of Limpopo, 2012.
Keywords: Vitamin B12; Holotranscobalamin